Checklist and annotated bibliography of decapod crustacean larvae from the Southwestern European coast (Gibraltar Strait area) - González Gordillo, J. I.; Dos Santos, A.; Rodríguez, A. (Scientia Marina, 2001)
Studies on decapod larvae entailing identification of specimens collected from plankton should be based on sound bibliographic sources that contain morphological descriptions of the species cited in the area. In order to facilitate this bibliographic search, we present a survey of the literature in which decapod larvae from the Gibraltar Strait area (encompassing most of the Mediterranean and northeastern Atlantic decapod crustacean species) are partially or completely described. Among these, the most accuratly identified larval specimens are pointed out. For each original case the taxon assigned by the author, types and numbers of stages described and the origin of the studied larvae are noted. Morever, a checklist of 377 species is given for Gibraltar Strait decapod crustaceans. Of all the species recorded in the area, larval descriptions are known, at least partially, for 220 species (58,35 %), but for 36 (9,54 %) morphological descriptions are sufficiently accurate for a correct identification from plankton specimens.